Nationwide surveillance for S-Metoprolol treatment effect on blood pressure control against sympathetic overdrive in Indian patients with hypertension (PROTECT) - Ramesh, D.; Kumar, Parminder Singh; Palimkar, Priya; Dhoot, Krishna; Dabhade, Dhammdeep C.; Newale, Sanket (International Journal of Advances in Medicine, 2022)
Background: Patients with hypertension in India been reported with high heart rate owing to sympathetic overdrive (SO). Beta-blockers provides several positive effects to reduce SO in patients with hypertension. The aim of present survey study was to understand current real-world prevalence of SO in Indian patients with hypertension and usage of beta-blocker therapy in them. Methods: A cross sectional, observational, questionnaire-based survey conducted across India between June 2020 to October 2020. A specially designed validated questionnaire was shared with 157 registered health care practitioners (HCP), their anonymous inputs were captured and analysed in qualitative manner. Categorical data was summarized by number (n) and percentage (%). Results: Total 157 HCP participated and completed the survey. Around 53% of HCP observed that patients with average heart rate above 75 beats/min were associated with negative prognosis. Around 43% of HCP reported that raised heart rate is associated with advanced age and increased body mass index (BMI). Two-third of HCP reported that tachycardia is associated with stage-2 hypertension and marked by restlessness and anxiety which is suggestive of SO. Over 70% HCP agreed that the HR below 75 beats/min is associated with good prognosis. Around 89% HCP reported beta-blockers as the drug of choice in patients with augmented SO. S-Metoprolol was reported to be the most preferred beta-blocker agent and was recommended by 76% HCP in patients with hypertension and coexisting SO. Conclusions: SO been reported prevalent condition in Indian patients with hypertension which likely worsens the prognosis in these patients. Beta-blockers reported to be the preferred choice of anti-hypertensive and S-Metoprolol seem to be the most preferred agent amongst the available beta-blockers against SO in patients with hypertension in India.